Empirically based rainfall threshold for landslides occurrence in Cameron Highlands, Malaysia - Abu Mansor, Abdul Muaz; Kasim, Norhidayu; Abu Taib, Kamarudin; Wan Azahar, Wan Nur Aifa; Ahmad Tajuddin, Husna (Springer Nature, 2021)
High-intensity rainfall has been recognized as the main factor of the landslide events in Cameron Highlands. Locating at an abrupt altitude with high intensity rainfall annually caused many attempts of slope failures in this area. This catastrophe weakens the socio-economy and situates the people of Cameron Highlands in difficulty since they lost their source of income. The application of the early warning system is one of the effective methods to reduce the losses from this unforeseen circumstance. It could be coordinated by developing a dependable rainfall intensity-duration (I-D) threshold for estimating the shallow landslide. By identifying twelve historical landslides in Cameron Highlands, the important variables from the rainfall intensity-duration parameter can be acquired. The proposed empirical rainfall intensity-duration (I-D) threshold for Cameron Highlands has been figured out as 0..075 I D 29.09 − = (I = rainfall intensity in mm/hr and D = duration in hour). Furthermore, to identify the formulation of I-D threshold from other regions, a comparison has been carried out by identifying the I-D threshold proposed by various researchers, which shows a reasonably higher value for the I-D thresholds of Cameron Highlands. This trend occurs due to the fact that rainwater requires more time to adequately seep into the thicker layer of soil in order to trigger the slope failure.